2021
DOI: 10.1128/mbio.02531-20
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for a Neutralizing Antibody Response Elicited by a Recombinant Hantaan Virus Gn Immunogen

Abstract: The spillover of pathogenic hantaviruses from rodent reservoirs into the human population poses a continued threat to human health. Here, we show that a recombinant form of the Hantaan virus (HTNV) surface-displayed glycoprotein, Gn, elicits a neutralizing antibody response in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 95 publications
1
23
0
Order By: Relevance
“…The preponderance of group I nAbs in our panel, together with recent descriptions of nAbs elicited against HTNV Gn/Gc that recognize overlapping or adjacent sequences in Gn H ( 40 ), suggest that this region of Gn, well-exposed on viral particles, is a major target of the antibody response to Gn/Gc in mammals, although it has not been described in earlier work aimed at identifying neutralizing epitopes ( 41 ). Here, we present new evidence that these mAbs exhibit at least two distinct binding modes, exemplified by ADI-37236 and previously reported mAbs ( 40 ) on the one hand and ADI-42898 on the other. Despite escaping binding and neutralization via similar mutations in the capping loop, ADI-37236 could bind both monomeric Gn H and heterodimeric Gn H /Gc proteins, whereas ADI-42898 could only bind Gn H /Gc (fig.…”
Section: Discussionmentioning
confidence: 71%
“…The preponderance of group I nAbs in our panel, together with recent descriptions of nAbs elicited against HTNV Gn/Gc that recognize overlapping or adjacent sequences in Gn H ( 40 ), suggest that this region of Gn, well-exposed on viral particles, is a major target of the antibody response to Gn/Gc in mammals, although it has not been described in earlier work aimed at identifying neutralizing epitopes ( 41 ). Here, we present new evidence that these mAbs exhibit at least two distinct binding modes, exemplified by ADI-37236 and previously reported mAbs ( 40 ) on the one hand and ADI-42898 on the other. Despite escaping binding and neutralization via similar mutations in the capping loop, ADI-37236 could bind both monomeric Gn H and heterodimeric Gn H /Gc proteins, whereas ADI-42898 could only bind Gn H /Gc (fig.…”
Section: Discussionmentioning
confidence: 71%
“…Epitopes are located on the outer surface of Gn and Gc glycoproteins. The crystal structure of the Gn complex with a neutralising antibody showed that the epitope includes positively charged amino acid at residues 83-85 [34]. This epitope can potentially serve as a binding site for a 2O-sulphated tetrasaccharide.…”
Section: Computer Modelling 231 Molecular Docking Of 2o-sulphated Fucooligosaccharide With the Integrin β3 Epitopementioning
confidence: 99%
“…SNV-24 bound to Gc domain I, an epitope that is only accessible in the pre-fusion state of Gc and is near the interface between inter-spike Gc heterodimers. P-4G2 (a bank vole-derived mAb) 12 and group II human PUUV mAbs described previously 16 also map to a similar site on Gc. This site has limited accessibility in the full virus lattice structure due to neighboring interspike contacts and may results in the incomplete neutralizing activity to authentic virus we demonstrated by these mAbs previously 18 .…”
Section: Resultsmentioning
confidence: 79%
“…Recent efforts have identified features of the molecular basis of neutralization by some antibodies targeting HTNV Gn 12 or PUUV Gc 13 . A rabbit-derived antibody, HTN-Gn1, targets domain A on Gn and overlaps with the putative binding sites for other murine-derived HTNV 14 and ANDV mAbs 15 .…”
Section: Mainmentioning
confidence: 99%